Immunological aspects of Alpha 1 Antitrypsin in COVID-19 infection among the Populace and Pregnant Women: Alpha 1 Antitrypsin and COVID-19 - Hassan, Wassan Nori; Najm, Mazin A. A.; Hasan, Alaa Hussein; Oudah, Khulood H. (AL-Kindy College Medical Journal, 2021)
Since the COVID-19 pandemic alarm was made by the severe acute respiratory syndrome (SARS)-coronavirus (CoV) 2, several institutions and agencies have pursued to clarify the viral virulence and infectivity. The fast propagation of this virus leads to an unprecedented rise in the number of cases worldwide. COVID-19 virus is exceptionally contagious that spreads through droplets, respiratory secretions, and direct contact. The enveloped, single-stranded RNA virus has a specific envelop region called (S) region encoding (S protein) that specifically binds to the host cell receptor. Viral infection requires receptors' participation on the host cell membrane's surface, a  key- step for the viral invasion of susceptible cells.Recently, the Italian alpha 1 antitrypsin  Registry results showed a close geographic distribution of positive cases like the one recorded for SARS -CoV-2 infection. AAT deficient patients presented with the highest infection rates. They were giving attention to alpha 1 antitrypsin AAT's role in COVID-19 infection. Alpha 1 antitrypsin deficiency (AATD) is undoubtedly the most common genetic condition in adults. AATD is characterized by decreased serum levels or impaired AAT action, raising the risk of developing many diseases, particularly pulmonary emphysema cirrhosis of the liver. This review will discuss the main immunological properties that AAT has as a protective agent against the infection and possible therapeutic application.